Theoretical Study on Concentration Monitoring of Suspended Particles by Laser Scattering Method - LIU Yong-jie; YU Xiao-yu; SUN Xu; SHI Yun-bo (Journal of Harbin University of Science and Technology)
Suspended particles detection is an important indicator of environmental pollution detection. Aiming at the measurement of suspended particles in the air, a theoretical design method is studied in this paper, which is based on the laser scattering method to measure the concentration of suspended particles. Firstly, the theory of particle concentration measurement based on laser scattering method is used for Mie scattering theory. Secondly, the light scattering properties of suspended particulate matter has been analysed, through the MATLAB simulation different characteristic parameters of a single suspended particle scattering light intensity distribution curve and extinction coefficient, get the relationship between the scattered light intensity distribution and the incident wavelength λ, the refractive index m (real part and imaginary part) and the particle size α. Finally, based on the simulation results, the particle size distribution is retrieved by the genetic algorithm, and the reliability of the scheme is proved by the inversion results. The verification shows that the method can accurately measure the mass concentration of suspended particulate matter.